Crop biotechnology: a pivotal moment for global acceptance. (2nd February 2016) - Hallerman, Eric; Grabau, Elizabeth
Abstract: The development and judicious use of agricultural biotechnology offers important contributions to food security and sustainability. Key contributions include improved yield, heightened pathogen and herbivore resistance, enhanced nutrient content, improved product quality, reduced spoilage, as well as entirely new traits. While a first wave of genetically engineered (GE) crop products has been commercialized and contributed to yield, other products – some posing significant benefits to target populations in the developing world – have become mired in controversy. Public misconception about nutritional and ecological risks, fears about multinational corporate dominance, as well as regulatory inaction have delayed the approval and use of GE crops. With new GE lines ready to pass through regulatory oversight, many of which originate from developing countries, we regard this as a pivotal moment for global acceptance of agricultural biotechnology. However, we note that some countries, international regulators, and even biotechnology companies seem willing to forego useful applications of GE crops. We conclude that educating and informing the public to combat misperception, and implementing review of regulatory guidelines based on decades of experience can help to realize the benefits of GE for food security, human well‐being, and ecological sustainability. Abstract : The development of GE crops offers the potential for many important contributions to food security but has become mired in controversy. Public misconception and regulatory inaction have contributed to delays in realizing the benefits of GE crops for food security, human well‐being, and ecological sustainability.